Strategies for diversifying income sources in Iraqi sports clubs and their impact on reducing dependence on government support (The International Journal for Scientific Research, 2026)
This research aims to identify strategies for diversifying income sources in Iraqi sports clubs and their impact on reducing reliance on government funding. The researcher employed a descriptive-analytical approach. The sample consisted of (120) administrative board members. Findings revealed a significant weakness in income diversification, with over 80% reliance on government grants. The study concluded that there is a statistically significant correlation between implementing sports investment strategies and achieving financial independence.
Keywords: Sports Investment; Self-funding; Iraqi Clubs; Sports Economics